Performance Profiling—Perspectives for Anti-doping and beyond - Iljukov, Sergei; Schumacher, Yorck O. (Frontiers in Physiology, 2017)
Performance profiling is a new area of research that could potentially open new frontiers in the fight against doping. The backbone of performance profiling in anti-doping is the individual tracking of performance through competition results or other metrics of sporting achievements. Since performance improvement is the primary goal of doping, it is expected that doping will affect competition results. Thus individual tracking of performance could potentially expose suspicious cases that deserve more scrutiny from anti-doping officials. On the other hand changes in performance levels could also be used to assess the efficiency of anti-doping strategies. Another application of performance analysis is to develop classifications of athletes according to level of performance. This classification has numerous practical meanings and provides an opportunity to set exact criteria for athletes belonging to national and international testing pools. At the moment there are no exact criteria for testing pool and doping test numbers needed. Thus, it creates inequality between nations and affects the credibility of the anti-doping system worldwide. Such classification would allow a more efficient use of anti-doping resources. Since doping is not the only threat to the integrity of sports, performance profiling can also help to reveal cases of other misbehavior in sports, like match fixing or result manipulation. In summary, performance modelling and its application to various fields is a new method to improve the efficiency of systems to safeguard the integrity of sports at different levels.